Near-band gap luminescence at room temperature from dislocations in silicon - Stowe, D; Galloway, SA; Senkader, S; Mallik, K; Falster, R; Wilshaw, P (2003)
Cathodoluminescence (CL) has been used to investigate room-temperature light emission from dislocations generated by ion-implantation. Czochralski silicon wafers were implanted with boron and silicon ions at a range of doses and energies to produce, after suitable thermal annealing, a band of dislocation loops typically similar to 150 nm from the surface. Room-temperature CL from specimens with a range of dislocation densities was observed with a peak wavelength of 1154 nm. The luminescence was found to be independent of the presence of a p-n junction and the luminescence efficiency was lower for the relatively lowly doped silicon implanted samples than in the case of the highly doped boron implanted samples. We attribute the luminescence behaviour to electron-hole recombination at the dislocations themselves and propose a model for this near-band gap luminescence based on one-dimensional energy bands previously associated with the strain field of dislocations. (C) 2003 Elsevier B.V. All rights reserved.